Trialkoxy functionalized polysiloxane as well as preparation method and application thereof
By using trialkoxy functionalized polysiloxane in thermal interface materials to react with hydroxyl groups on the surface of inorganic filler, a hydrophobic organic layer is formed, which solves the problems of uneven dispersion of fillers and low thermal conductivity, and achieves higher filling Coefficients and thermal conductivity.
Patent Information
- Application Number
- CN202411654780.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
During the preparation process, the existing thermal interface materials are difficult to disperse the filler evenly due to the presence of hydroxyl groups on the surface of the inorganic filler, and are prone to sedimentation and powdering, and have a low thermal conductivity.
Using trialkoxy functionalized polysiloxane, the trialkoxy groups in the middle of its segment are designed to react with the hydroxyl groups on the surface of the inorganic filler to form hydrophobic polysiloxane segments on the surface of the filler and The organic layer composed of methyl groups improves the compatibility of the filler and the polysiloxane matrix.
Effectively reduce the hydroxyl content on the surface of the filler, improve the dispersion and filling coefficient of the filler in the polysiloxane matrix, enhance the thermal conductivity of the thermal interface material, reduce the possibility of particle settlement, and improve the flexibility of the material. and needle inlet.
Smart Images

Figure CN119463184A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal interface materials, and in particular to a trialkoxy functionalized polysiloxane and a preparation method and application thereof. Background Art
[0002] Silicon-based thermal interface material, also known as TIM1, is made of polysiloxane as the base polymer and inorganic fillers with high thermal conductivity such as alumina, aluminum nitride, and silicon carbide as fillers. The inorganic fillers are uniformly dispersed in the polysiloxane matrix by mechanical means. According to the degree of cross-linking and curing of polysiloxane, it is divided into non-cross-linked thermal conductive silicone paste, partially cross-linked thermal conductive gel, and fully cross-linked silicone gasket. It is used for contact heat dissipation between heat sources such as high-power LED chips, 5G and 6G chips, and computer CPU chips and heat dissipation bases to remove the low thermal conductivity air filled between the heat source and the heat dissipation base, so that the heat generated by the heat source can be removed in time through heat conduction, ensuring the continuous and stable operation of electronic components and assemblies.
[0003] The surface of inorganic fillers contains hydrophilic hydroxyl groups. On the one hand, the presence of hydroxyl groups causes fillers to form agglomerates through hydrogen bonds, making it difficult for fillers to be evenly dispersed in the polysiloxane matrix; on the other hand, the polarity of these hydroxyl groups is very different from that of polysiloxane, resulting in uneven dispersion of inorganic fillers in the polysiloxane matrix. When the inorganic fillers are mixed with the polysiloxane matrix in a low dose, the inorganic fillers are easily separated from the polysiloxane matrix, and after being placed for a period of time, the fillers will settle. When the filling ratio of inorganic fillers is increased, the fillers will not be evenly dispersed in the polysiloxane matrix due to the agglomeration of fillers caused by hydrogen bonds formed by hydroxyl groups on the filler surface and the difference in polarity between the fillers and the polysiloxane matrix. The prepared thermal interface material will show abnormal phenomena such as powdering or hardening, which cannot meet the actual application requirements.
[0004] In order to overcome the above abnormal phenomenon, those skilled in the art usually use silane coupling agents to treat the surface of the filler. As is known to all, silane coupling agents are a type of substance that contains an alkoxy group that can react with the hydroxyl group on the surface of the inorganic filler at one end of the molecular chain and an active organic functional group at the other end of the molecular chain. By treating the inorganic filler with a silane coupling agent, an organic layer can be coated on the surface of the inorganic filler, thereby effectively reducing the hydroxyl content on the surface of the filler, improving the dispersion of the filler in the polysiloxane matrix, and especially increasing the filling factor of the filler in the polysiloxane matrix.
[0005] CN118085295A discloses a thermal interface material and its preparation method and application. The raw materials for preparing the thermal interface material include the following components: side chain hydrogenated polydimethylsiloxane, double-terminal vinyl polydimethylsiloxane, spherical aluminum powder, and catalyst; the hydrogen functionality of the side chain hydrogenated polydimethylsiloxane is 9-200; in the system composed of the side chain hydrogenated polydimethylsiloxane and double-terminal vinyl polydimethylsiloxane, the molar ratio of vinyl to side chain hydrogen is 0.2-0.8; the spherical aluminum powder includes a combination of spherical aluminum powders with particle sizes of 0.5-2μm, 8-12μm, 16-24μm, and 40-60μm, respectively. The thermal interface material provided by the present invention has high toughness, high adhesion, and high thermal conductivity.
[0006] Although the use of silane coupling agent as an inorganic filler surface treatment agent effectively reduces the hydroxyl content on the surface of the inorganic filler and the powder agglomeration and dispersion problems caused by it in the polysiloxane matrix, the polarity of the organic functional group contained in the commercial silane coupling agent molecule and the polysiloxane matrix is still quite different, resulting in the thermal interface material prepared with the inorganic filler treated with the commercial silane coupling agent still having defects such as phase separation, low filler filling factor and low thermal conductivity of the prepared thermal interface material. Summary of the invention
[0007] In order to overcome the technical defects of easy sedimentation of fillers and low filling coefficient when using commercial silane coupling agents as surface treatment agents for inorganic fillers, the present invention provides a trialkoxy functionalized polysiloxane, in which the trialkoxy group in the middle of the chain segment can react with the hydroxyl group on the surface of the inorganic filler, thereby improving the compatibility stability of the filler and the polysiloxane matrix and preventing sedimentation.
[0008] To achieve the above object, the technical solution adopted by the present invention is: A trialkoxy functionalized polysiloxane having the structural formula shown below:
[0009] Among them, R a is one of methyl, ethyl, phenyl, vinyl, butyl or trimethylsilyl; R b is at least one of methyl, ethyl, phenyl or trifluoropropyl; R c is at least one of methyl, ethyl, phenyl or trifluoropropyl, R d is at least one of methyl, ethyl, propyl or phenyl, R e is methyl or ethyl; m is R b R c The degree of polymerization of the SiO chain segment, m, is 2~500.
[0010] The present invention designs a trialkoxy group in the middle segment of the polysiloxane, which can react and connect with the hydroxyl group on the surface of the filler, and coats the surface of the filler with an organic layer composed of two hydrophobic polysiloxane segments and one methyl group. Since the polysiloxane segments generated on the surface of the filler have the same molecular structure as the polysiloxane matrix, the inorganic filler treated by this technical solution not only has good stability and is not easy to settle in the polysiloxane matrix, but also has a higher filling factor, and is particularly suitable for preparing thermal interface materials with high thermal conductivity. Compared with the alkoxy group at the end group position, the organic segment after successful grafting is like "two hands" surrounding the surface of the filler, which can achieve a better wrapping effect, enhance the interface interaction between the filler surface and the matrix, form a good thermal conductivity path, and reduce the possibility of particle sedimentation.
[0011] Preferably, the R a is methyl, vinyl or butyl, R b , R c , R d is methyl or ethyl, R e It is methyl.
[0012] Preferably, m is 2 to 50. In particular, when m=9, the thermal conductivity of the prepared silicone paste can reach 9.1190 W / (m·K), and the 1 / 4 cone penetration can still be maintained at about 55.0.
[0013] The present invention also provides a method for preparing the trialkoxy-functionalized polysiloxane, comprising the steps of: Step 1, alkyl lithium RaLi is activated in a solvent, and a solution of cyclotrisiloxane shown in formula I is added to perform polymerization reaction to obtain intermediate A. After the reaction is completed, a solution of dichlorosilane shown in formula II is added to continue the reaction, and intermediate B is obtained by purification; the reaction formula is shown below:
[0014]
[0015] Step 2, activating the intermediate B and the Custer catalyst, adding trialkoxysilane YSi(ORe)3 to catalyze the reaction, and purifying to obtain the trialkoxy functionalized polysiloxane; the reaction formula is as follows: .
[0016] The structural formulas of the cyclotrisiloxane shown in formula I, the intermediate A, the dichlorosilane shown in formula II and the intermediate B are as follows: .
[0017] wherein Ra, Rb, Rc, Rd and Re are as described above, m is 2 to 500, and X and Y are H or vinyl, which are different.
[0018] In step 1, the solvent of alkyl lithium RaLi, cyclotrisiloxane and dichlorosilane is an ether solvent; the ether solvent includes at least one of diethyl ether, dimethyl ether, diethoxymethane, tetrahydrofuran, methyltetrahydrofuran and 1,4-dioxane.
[0019] The alkyl lithium RaLi includes at least one of methyl lithium, ethyl lithium, phenyl lithium, n-butyl lithium, dimethyl vinyl silicon alkoxide lithium, and trimethylsilyl methyl lithium; Preferably, the volume ratio of the molar number of the alkyl lithium to the ether solvent in step 1 is 1.0×10 -3 ~5.0×10 -3 mol / mL; the mixing temperature of the ether solvent and the alkyl lithium is -15~15°C, and the holding time of the mixture of the ether solvent and the alkyl lithium at the mixing temperature is 10~240 min; The cyclotrisiloxane is selected from at least one of hexamethylcyclotrisiloxane, hexaethylcyclotrisiloxane, 1,3,5-trimethyl-1,3,5-triethylcyclotrisiloxane, 1,3,5-trimethyl-1,3,5-triphenylcyclotrisiloxane, and hexaphenylcyclotrisiloxane; Preferably, in the mixed solution of cyclotrisiloxane and ether solvent, the mass ratio of cyclotrisiloxane to the volume ratio of ether solvent is 0.50-5.0 g / mL; the addition time of the mixed solution of cyclotrisiloxane and ether solvent is 5-120 min; The dichlorosilane is selected from at least one of methyldichlorosilane, methylvinyldichlorosilane, ethyldichlorosilane, ethylvinyldichlorosilane, phenyldichlorosilane and phenylvinyldichlorosilane.
[0020] In step 1, the polymerization reaction temperature is 15-50°C, and the reaction time is 4-36 h; preferably, the reaction temperature is 15-40°C, and the reaction time is 5-27 h; The molar ratio of the alkyl lithium to the cyclotrisiloxane is 1:0.1 to 1:120; The molar ratio of dichlorosilane to alkyl lithium is 0.25-0.75:1, the addition time of dichlorosilane is 2-60 min, and the reaction time after adding dichlorosilane is 10-180 min. Preferably, the molar ratio of dichlorosilane to alkyl lithium is 0.40-0.60:1, the addition time of dichlorosilane is 4-45 min, and the reaction time after adding dichlorosilane is 20-120 min;
[0021] In step 2, the molar ratio of trialkoxysilane to intermediate B is 1.25 to 2.50:1; preferably, the molar ratio is 1.35 to 2.00:1; The catalyst activation temperature is 60~90℃; the activation time is 20~60 min; The catalytic reaction temperature is 60~90℃ and the reaction time is 1~12h.
[0022] The mass of platinum in the Custer catalyst is 2.5×10 -6 ~100×10 -6 Preferably, the mass of platinum in the Custer catalyst is 5.0×10 of the total mass of the reaction raw materials. -6 ~50×10 -6 After the reaction in step 2 is completed, an organic amine is added to deactivate the catalyst. The organic amine is selected from at least one of triethylamine, ethylenediamine, diethylamine, and aniline; the mass is 3.0×10 of the total mass of the reaction raw materials. -4 ~50×10 -4 .
[0023] After the reaction in step 1 is completed, the solvent and impurities are removed by vacuum distillation; preferably, after a vacuum distillation, the salt is filtered and removed, and then a second vacuum distillation is performed to obtain the intermediate B; the first vacuum distillation pressure is -95~-75 kPa, the temperature is 60~90°C, and the time is 1.5~5.0 h; the second vacuum distillation pressure is -101.2~-95 kPa, the temperature is 140~200°C, and the time is 2.0~8.0 h.
[0024] After the reaction in step 2 is completed, the crude product is subjected to vacuum distillation to purify the product, the vacuum distillation operation pressure is -101.2~-90 kPa, the vacuum distillation temperature is 120~200 °C, and the vacuum distillation time is 1~12 h.
[0025] The invention also provides a thermal interface material, comprising a double-end trimethylsiloxy-terminated polydimethylsiloxane, an aluminum oxide filler and the trialkoxy-functionalized polysiloxane.
[0026] Compared with the prior art, the present invention has the following beneficial effects: (1) Using trialkoxy-functionalized polysiloxane to treat the surface of inorganic fillers can effectively reduce the hydroxyl content on the filler surface and graft polysiloxane segments on the filler surface, so that inorganic fillers with high filling ratios can be evenly dispersed in the polysiloxane matrix without powdering and hardening; (2) Using trialkoxy-functionalized polysiloxane instead of the existing silane coupling agent to treat the surface of the inorganic filler can not only reduce the hydroxyl content on the filler surface and make the treated thermally conductive filler evenly dispersed in the polysiloxane matrix, but also improve the thermal conductivity of the prepared thermal interface material, reduce thermal resistance, and at the same time improve the flexibility of the thermal interface material and increase needle penetration. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The trimethoxy functionalized polysiloxane prepared in Example 1 1 H NMR spectrum.
[0028] Figure 2 The trimethoxy functionalized polysiloxane prepared in Example 1 29 Si NMR spectrum.
[0029] Figure 3 FT-IR spectra of untreated 120 μm alumina (A), trimethoxy-functionalized polysiloxane prepared in Example 4 (B), and silicone paste prepared in Example 4 (C).
[0030] Figure 4 The trimethoxy-functional polysiloxane prepared in Example 6 1 H NMR spectrum.
[0031] Figure 5 The trimethoxy-functional polysiloxane prepared in Example 6 29 Si NMR spectrum.
[0032] Figure 6 The trimethoxy-functional polysiloxane prepared in Example 7 1 H NMR spectrum.
[0033] Figure 7 The trimethoxy-functional polysiloxane prepared in Example 7 29 Si NMR spectrum. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0035] 1 H NMR test: The liquid sample to be tested was dissolved in deuterated chloroform (CDCl3) without internal standard solvent and measured using AVANCE AV Ⅲ 400 MHz NMR instrument produced by Bruker, Germany. 1 H NMR test.
[0036] 29Si NMR test: The sample was dissolved in deuterated chloroform (CDCl3) solvent without internal standard and tested using a 500 MHz nuclear magnetic resonance spectrometer (AVANCE Ⅲ) from Bruker, Germany.
[0037] FT-IR spectrum: The KBr tablet method was used to prepare the sample for FT-IR spectrum testing, with a wave number range of 4000~400 cm -1 , scan times 32, resolution 4 cm -1 .
[0038] GPC test: PL-GPC50 gel permeation chromatograph was used, with polydimethylsiloxane with known molecular weight (490, 6200, 15000, 34100, 64800, 95800, 219400, 384500 and 610000 g / mol, American Polymer Standards Company) as standard samples, toluene as mobile phase, flow rate of 1.0 mL / min, column temperature of 25 °C, and molecular weight was calculated based on the time it took for the sample to flow out of the chromatographic column relative to the time it took for the standard sample to flow through.
[0039] Dynamic viscosity test: According to GB / T2794-2013 standard, the American Bookfeild DV2TRVTJ0 rotational viscometer was used to measure the viscosity at a constant temperature of 25±0.1℃ and a rotation speed of 200 rpm. The test time was 5 min and the uncertainty of the dynamic viscosity was 1%.
[0040] Preparation of thermal conductive silicone paste samples: Use the ZYMC-180HV non-invasive homogenizer produced by Shenzhen Zhongyi Technology Co., Ltd. to add double-ended trimethylsiloxy-terminated polydimethylsiloxane as the base silicone oil into the mixing cup, add the trialkoxy functionalized polysiloxane prepared in this application as the surface treatment agent for the thermal conductive filler, place the cup on the rotating fixed frame in the instrument, and mix for 1 min at a speed of 1800 rpm and under the condition of reduced pressure to -99.5 kPa; take out the evenly mixed cup, add a filler composed of spherical Al2O3 particles of different particle sizes at one time or in batches, and then place the cup in a non-invasive homogenizer and mix for 3 min under the same conditions to obtain a thermal conductive silicone paste sample for testing.
[0041] Thermal conductivity test of silicone paste: DRL-III instrument produced by Xiangtan Xiangyi Instrument Co., Ltd. was used to test according to ASTMD5470. The thermal conductive silicone paste was applied to a nylon plastic tube with an inner area of about 615 mm 2 , test thickness 2~3 mm, set pressure 30 N, cold pole temperature 20 ℃, hot pole temperature 80 ℃, test the thermal conductivity and thermal impedance of the sample after the temperature stabilizes for 200 s.
[0042] Cone penetration test: According to GB / T 269-2023 "Determination of cone penetration of greases and petroleum greases", the WM-221A of Guangdong Wanmu Instrument Co., Ltd. is used to test the cone penetration value of a 1 / 4 cone falling for 5 s in an environment of 25 ℃.
[0043] Example 1 Preparation of trimethoxy-functionalized polydimethylsiloxane with double-terminal trimethylsilyl end-capped with a polymerization degree (m=3) S1: Add 200.0 mL of tetrahydrofuran with a water content of less than 200 ppm to a 2L dry three-necked flask at 0°C under nitrogen protection while stirring, then add 269.7 mL (0.674 mol) of a 2.5 mol / L methyllithium diethoxymethane solution to the three-necked flask, stir and maintain at this temperature for 60 min; add a mixed solution consisting of 150.0 g (0.674 mol) of hexamethylcyclotrisiloxane and 150.0 mL of tetrahydrofuran with a water content of less than 200 ppm to the three-necked flask dropwise over 15 min. After the addition of the THF solution of hexamethylcyclotrisiloxane is completed, the temperature of the reaction mixture is raised to 25°C and the reaction is continued at this temperature for 6 h; when the raw material point disappears as monitored by thin layer chromatography (TLC), add 39.5 g (0.343 mol) of methyldichlorosilane (MeHSiCl2) for bridging reaction, and the addition time is 5 min. min; after the addition of methyldichlorosilane was completed, the reaction mixture was allowed to react at 25°C for 30 min.
[0044] S2: The crude reaction product obtained in S1 was subjected to vacuum distillation at a pressure of -85 kPa from room temperature to 70 °C for 2 h. After removing low boiling point solvents such as tetrahydrofuran, the liquid in the kettle was cooled to room temperature. The produced salt was removed by vacuum filtration. The resulting colorless and transparent mixed solution was then subjected to vacuum distillation at a pressure of -100 kPa and 160 °C for 3 h to remove high boiling point substances. After cooling to room temperature, 154.21 g of colorless and transparent double-terminal trimethylsilyl-terminated Si-H functionalized polysiloxane intermediate was obtained with a yield of 88.2%. Its chemical structure is shown in Formula (B-1).
[0045] (B-1) Wherein m represents the degree of polymerization of the dimethylsiloxy chain segment.
[0046] S3: Dry nitrogen was introduced into a dry 100 mL three-necked flask, and then 30.0 g (0.0405 mol) of the Si-H functionalized polysiloxane intermediate (B-1) capped with double-end trimethylsilyloxy groups obtained in step S2 and 0.78 g (the effective content of platinum atoms was 20 ppm) of Karstedt catalyst with a platinum content of 0.1 wt% were added, and the temperature was raised to 70 °C with stirring, and activated at this temperature for about 30 min; 9.1 g (0.0615 mol) of vinyltrimethoxysilane was added to the three-necked flask through a syringe pump over 20 min. After the addition of vinyltrimethoxysilane, the reaction mixture was allowed to react at 70 °C for 5 h. S4: After the reaction of S3 is completed, the crude reaction product is cooled to room temperature, and 0.05 g of triethylamine is added to the crude reaction product to inactivate the residual platinum catalyst; the reaction mixture is then subjected to reduced pressure distillation at -100 kPa and 140 °C for 4 h, and after removing low-boiling substances, 34.11 g of light yellow, clear and transparent double-terminal trimethylsilyl-terminated trimethoxy-functionalized polysiloxane is obtained with a yield of 95.9%. Its chemical structure is shown in formula (III).
[0047] (III) Wherein m is the degree of polymerization of the dimethylsiloxy chain segment.
[0048] The product prepared in Example 1 was 1 H NMR analysis, the results are as follows Figure 1 The peak with a chemical shift of about δ = 0.085 ppm is all methyl groups connected to silicon atoms (Si-C H 3) The proton peak on the molecule; the chemical shift at about δ=0.57 ppm is the characteristic peak of the product after anti-Markovnikov addition; the chemical shift at about δ=1.09 ppm is the characteristic peak of the product after Markovnikov addition; the chemical shift at δ=3.56 ppm is the chemical shift of the proton on the trimethoxy group (-Si-OC H 3). Define the integral area of Si-OCH3 as 9, then the proton peak area of all silicon methyl groups is 56.9. According to the formula for calculating the structural polymerization degree m, 3+2×(6m+9)=56.9, we can get m≈3.
[0049] Product 29 Si NMR spectrum Figure 2 As shown, the peak with a chemical shift of about δ = 7.2 ppm comes from -O- Si The characteristic peak of silicon atom in -(CH3)3, the peak with chemical shift around δ=-21.4 ppm is the D chain -O- SiThe characteristic peak of silicon atom in -(CH3)2-O-, with chemical shift at δ=-41.4 ppm is - Si -Characteristic peaks of silicon atoms in (OCH3)3.
[0050] GPC analysis of the product showed that the number average molecular weight (Mn) of the polymer was 741 g / mol and the polydispersity index (PDI) was 1.24. The viscosity of the polymer at 25 °C was 9.25 mPa·s as measured by a rotational viscosity instrument.
[0051] Preparation of thermal conductive silicone paste sample: Add 1.76 g of trimethoxy functionalized polysiloxane terminated with trimethylsiloxy groups prepared in Example 1, 1.12 g of dimethyl silicone oil with a viscosity of 350 mPa.s at 25°C, 48.40 g of Al2O3 particles with an average particle size of 120 μm, 26.40 g of Al2O3 particles with an average particle size of 10 μm, and 13.20 g of Al2O3 particles with an average particle size of 0.5 μm into a mixing cup. The density of all polysiloxane fluids is 0.98 g / cm 3 Calculation: The density of Al2O3 thermal conductive fillers of various particle sizes is 4.0g / cm 3 Calculation shows that the volume fraction of alumina filled in the silicone paste is 88 vol%.
[0052] The mixing cup was placed on the sample fixture of the non-intrusive homogenizer and mixed for 3 min at a speed of 1800 rpm and reduced pressure to -99.5 kPa to obtain a thermal conductive silicone paste sample. Its performance test data is shown in Table 1.
[0053] Example 2 Preparation of trimethoxy-functionalized polydimethylsiloxane with double-terminal trimethylsilyl end-capped with a polymerization degree (m=6) The steps for preparing a trimethoxy-functionalized polydimethylsiloxane (m=6) terminated with trimethylsilyl groups at both ends are as follows: S1: This step is different from Example 1 in that helium is used as the protective gas in the three-necked flask at a temperature of -5°C; methyltetrahydrofuran having a water content of less than 200 ppm is used instead of tetrahydrofuran; the amount of 2.5 mol / L diethoxymethane solution of methyllithium is 179.8 mL (0.45 mol); 200.0 g (0.90 mol) of hexamethylcyclotrisiloxane and 200.0 mL of methyltetrahydrofuran having a water content of less than 200 ppm after redistillation are used to prepare a methyltetrahydrofuran solution of hexamethylcyclotrisiloxane; the amount of methyldichlorosilane is 26.4 g (0.23 mol), the addition time is 10 min, and after the addition of methyldichlorosilane is completed, the reaction mixture is continued to react at 25°C for 45 min.
[0054] S2: This step is the same as Example 1, and 195.31 g of colorless and transparent Si-H functionalized polysiloxane intermediate terminated with trimethylsilyl groups at both ends is obtained, with a yield of 90.2%.
[0055] S3: This step is different from Example 1 in that the amount of the intermediate product obtained in S1 in Example 2 is 40.0 g (0.031 mol), the amount of 0.1 wt% Karstedt catalyst (20 ppm) is 0.94 g, and the amount of vinyltrimethoxysilane is 7.0 g (0.047 mol).
[0056] S4: This step is different from Example 1 in that 0.05 g of ethylenediamine is used as a passivating agent for the platinum catalyst. 43.05 g of light yellow, clear and transparent trimethoxy-functionalized polysiloxane capped with trimethylsilyl groups at both ends is obtained, with a yield of 96.1%.
[0057] The product obtained in Example 2 was 1 H NMR test, by 1 The H NMR test results showed that the degree of polymerization of the product was m=6. The GPC analysis showed that the number average molecular weight (Mn) of the polymer was 1295 g / mol and the polydispersity index (PDI) was 1.31. The viscosity of the polymer at 25 °C was 13.50 mPa·s as measured by a rotational viscosity instrument.
[0058] The trimethoxy-functionalized polysiloxane with a polymerization degree of m=6 and double-end trimethylsiloxy-terminated was used instead of the trimethoxy-functionalized polysiloxane with a polymerization degree of m=3 and double-end trimethylsiloxy-terminated in Example 1 as the surface treatment agent for the alumina filler. The rest was the same as in Example 1 to prepare the thermal conductive silicone paste sample of Example 2, and its performance test data is shown in Table 1.
[0059] Example 3 Preparation of trimethoxy-functionalized polydimethylsiloxane with double-terminal trimethylsilyl end-capped with a polymerization degree (m=8) The steps for preparing a trimethoxy-functionalized polydimethylsiloxane (m=8) terminated with trimethylsilyl groups at both ends are as follows: S1: This step is different from Example 1 in that nitrogen is used as protective gas in a three-necked flask at a temperature of -10°C; 107.9 mL (0.27 mol) of 2.5 mol / L methyllithium diethoxymethane solution is used, the volume of THF mixed with the methyllithium reagent is 100 mL, and the water content is less than 200 ppm; 180.0 g (0.81 mol) of hexamethylcyclotrisiloxane and 180.0 mL of tetrahydrofuran with a water content of less than 200 ppm after redistillation are used to prepare a THF solution of hexamethylcyclotrisiloxane; the THF solution of hexamethylcyclotrisiloxane is added dropwise for 45 min; after the addition is completed, the temperature of the reaction mixture is raised to 35°C, and the reaction is continued at this temperature for 9 h; the amount of methyldichlorosilane is 15.9 g (0.138 mol), the addition time is 20 min, and after the addition of methyldichlorosilane is completed, the reaction mixture is continued to react at 35°C for 30 min.
[0060] S2: This step is the same as Example 1, and 170.40 g of colorless and transparent Si-H functionalized polysiloxane intermediate terminated with trimethylsilyl groups at both ends is obtained, with a yield of 89.7%.
[0061] S3: This step is different from Example 1 in that the amount of the intermediate product obtained in S1 in Example 3 is 50.0 g (0.026 mol), the amount of 0.1 wt% Karstedt catalyst (20 ppm) is 1.12 g, and the amount of vinyltrimethoxysilane is 6.2 g (0.042 mol).
[0062] S4: This step is the same as Example 2, and 53.55 g of light yellow, clear and transparent trimethoxy-functionalized polysiloxane capped with trimethylsilyl groups at both ends is obtained, with a yield of 97.6%.
[0063] The product obtained in Example 3 was 1 H NMR test, by 1 The H NMR test results showed that the degree of polymerization of the product was m=8. The GPC analysis showed that the number average molecular weight (Mn) of the polymer was 1914 g / mol and the polydispersity index (PDI) was 1.33. The viscosity of the polymer at 25 °C was 17.25 mPa·s as measured by a rotational viscosity instrument.
[0064] The trimethoxy-functionalized polysiloxane with a polymerization degree of m=8 and double-end trimethylsiloxy-terminated was used instead of the trimethoxy-functionalized polysiloxane with a polymerization degree of m=3 and double-end trimethylsiloxy-terminated in Example 1 as the surface treatment agent for the alumina filler. The rest was the same as in Example 1 to prepare the thermal conductive silicone paste sample of Example 3, and its performance test data is shown in Table 1.
[0065] Example 4 Preparation of trimethoxy-functionalized polydimethylsiloxane with double-terminal trimethylsilyl end-capped with a polymerization degree (m=14) The steps for preparing a trimethoxy-functionalized polydimethylsiloxane (m=14) terminated with trimethylsilyl groups at both ends are as follows: S1: This step is different from Example 1 in that nitrogen is used as the protective gas in the three-necked flask at a temperature of 10°C; the amount of 2.5 mol / L methyllithium diethoxymethane solution used is 71.9 mL (0.18 mol), the volume of THF mixed with the methyllithium reagent is 100 mL, and the water content is less than 200 ppm; 200.0 g (0.90 mol) of hexamethylcyclotrisiloxane and 200.0 mL of tetrahydrofuran with a water content of less than 200 ppm after redistillation are used to prepare a THF solution of hexamethylcyclotrisiloxane, and the addition time of the mixed solution is 30 min; after the addition of the THF solution of hexamethylcyclotrisiloxane is completed, the temperature of the reaction mixture is raised to 20°C and maintained at this temperature for 12 h; the amount of methyldichlorosilane used is 10.5 g (0.091 mol), the addition time is 30 min, and after the addition of methyldichlorosilane is completed, the reaction mixture is continued to react at 20°C for 90 min.
[0066] S2: This step is the same as Example 1, and 180.99 g of colorless and transparent Si-H functionalized polysiloxane intermediate terminated with trimethylsilyl groups at both ends is obtained, with a yield of 87.6%.
[0067] S3: This step is different from Example 1 in that the amount of the intermediate product obtained in S1 in Example 4 is 50.0 g, the amount of 0.1 wt% Karstedt catalyst (20 ppm) is 1.08 g, and the amount of vinyltrimethoxysilane is 4.2 g (0.028 mol).
[0068] S4: This step is the same as Example 2, and 51.31 g of light yellow, clear and transparent trimethoxy-functionalized polysiloxane capped with trimethylsilyl groups at both ends is obtained, with a yield of 96.7%.
[0069] The product obtained in Example 4 was 1 H NMR test, by 1 The H NMR test results showed that the degree of polymerization of the product was m=14. The GPC analysis showed that the number average molecular weight (Mn) of the polymer was 3060 g / mol and the polydispersity index (PDI) was 1.53. The viscosity of the polymer at 25 °C was 28.25 mPa·s as measured by a rotational viscosity instrument.
[0070] Figure 3FT-IR spectra of untreated 120 μm alumina (A), trimethoxy-functionalized polysiloxane prepared in Example 4 (B), and silicone paste prepared in Example 4 (C); it can be seen that the Si-OCH3 characteristic peak of the silicone paste prepared using the trialkoxy-functionalized polysiloxane disclosed in the present invention disappears, and characteristic peaks of Si-CH3 and Si-O-Si appear compared to the untreated alumina, which indicates that the trialkoxy-functionalized polysiloxane successfully reacts with the hydroxyl group on the filler surface and is grafted onto the filler surface.
[0071] The trimethoxy-functionalized polysiloxane with a degree of polymerization of m=14 and double-ended trimethylsiloxy-capped was used as the surface treatment agent for the alumina filler instead of the trimethoxy-functionalized polysiloxane with a degree of polymerization of m=3 and double-ended trimethylsiloxy-capped in Example 1. The rest was the same as in Example 1 to prepare the thermal conductive silicone paste sample of Example 4, and its performance test data is shown in Table 1.
[0072] Example 5 Preparation of trimethoxy-functionalized polydimethylsiloxane with double-terminal trimethylsilyl end-capped with a polymerization degree (m=37) The preparation of trimethoxy-functionalized polydimethylsiloxane (m=37) terminated with trimethylsilyl groups at both ends was carried out as follows: S1: This step is different from Example 1 in that the amount of 2.5 mol / L methyllithium diethoxymethane solution used is 45.0 mL (0.18 mol), the volume of THF mixed with the methyllithium reagent is 50 mL, and the water content is less than 200 ppm; 300.0 g (1.35 mol) of hexamethylcyclotrisiloxane and 300.0 mL of tetrahydrofuran with a water content of less than 200 ppm after redistillation are used to prepare a THF solution of hexamethylcyclotrisiloxane, and the addition time is 60 min. After the addition is completed, the temperature of the reaction mixture is raised to 25°C, and the reaction is continued at this temperature for 10 h; the amount of methyldichlorosilane used is 6.6 g (0.057 mol), and the addition time is 25 min. After the addition of methyldichlorosilane is completed, the reaction mixture is continued to react at 25°C for 45 min.
[0073] S2: This step is the same as Example 1, and 269.71 g of colorless and transparent Si-H functionalized polysiloxane intermediate terminated with trimethylsilyl groups at both ends is obtained, with a yield of 88.7%.
[0074] S3: This step is different from Example 1 in that the amount of the intermediate product obtained in S1 in Example 5 is 100.0 g, and 40.0 mL of toluene with a water content of less than 200 ppm is added at the same time, 2.07 g of 0.1 wt% Karstedt catalyst (20 ppm) is used, and 3.5 g (0.024 mol) of vinyltrimethoxysilane is used.
[0075] S4: This step is the same as Example 2. 100.91 g of light yellow, clear and transparent trimethoxy-functionalized polysiloxane capped with trimethylsilyl groups at both ends was obtained, with a yield of 98.4%.
[0076] The product obtained in Example 5 was 1 H NMR test, by 1 The H NMR test results showed that the degree of polymerization of the product was m=37. The GPC analysis showed that the number average molecular weight (Mn) of the polymer was 6774 g / mol and the polydispersity index (PDI) was 1.40. The viscosity of the polymer at 25 °C was 72.25 mPa·s as measured by a rotational viscosity instrument.
[0077] The trimethoxy-functionalized polysiloxane with a degree of polymerization of m=37 and double-ended trimethylsiloxy-capped trimethoxy-functionalized polysiloxane in Example 5 was used to replace the trimethoxy-functionalized polysiloxane with a degree of polymerization of m=3 in Example 1 as the surface treatment agent for the alumina filler. The rest was the same as in Example 1 to prepare the thermal conductive silicone paste sample of Example 5, and its performance test data is shown in Table 1.
[0078] Example 6 Preparation of trimethoxy-functionalized polydimethylsiloxane with dual-end dimethylvinylsiloxy end-capped with a polymerization degree of m=23 S1: Add 30.0 mL of tetrahydrofuran with a water content of less than 200 ppm to a 1L dry three-necked flask at -5°C under nitrogen protection while stirring, then add 56.3 mL (0.113 mol) of a 2.0 mol / L THF solution of lithium dimethylvinylsilanol into the three-necked flask, and stir and maintain at this temperature for 120 min; add a mixed solution consisting of 100.0 g (0.45 mol) of hexamethylcyclotrisiloxane and 100.0 mL of tetrahydrofuran with a water content of less than 200 ppm to the three-necked flask dropwise over 35 min. After the addition of the THF solution of hexamethylcyclotrisiloxane is completed, the temperature of the reaction mixture is raised to 30°C and the reaction is continued at this temperature for 7 h; when the raw material point disappears as monitored by thin layer chromatography (TLC), add 6.59 g (0.057 mol) of methyldichlorosilane (MeHSiCl2) for bridging reaction, and the addition time is 10 min; after the addition of methyldichlorosilane was completed, the reaction mixture was continued to react at 30 °C for 60 min.
[0079] S2: The crude product of S1 was subjected to vacuum distillation at a pressure of -85 kPa from room temperature to 70 °C for 3 h. After removing low boiling point solvents such as tetrahydrofuran, the liquid in the kettle was cooled to room temperature. After removing the generated salt by vacuum filtration, the obtained colorless transparent mixed solution was subjected to vacuum distillation at a pressure of -100 kPa and 160 °C for 4 h to remove high boiling point substances. After cooling to room temperature, 104.07 g of colorless transparent double-end dimethylvinylsiloxy-terminated Si-H functionalized polysiloxane intermediate was obtained with a yield of 91.7%. Its chemical structure is shown in formula (IV).
[0080] (IV) Wherein m represents the degree of polymerization of the dimethylsiloxy chain segment.
[0081] S3: Dry nitrogen was introduced into a dry 100 mL three-necked flask, and then 30.0 g of the Si-H functionalized polysiloxane intermediate terminated with dimethylvinylsiloxy groups obtained in step S2 and 0.33 g (effective content of platinum atoms was 10 ppm) of Karstedt catalyst with a platinum content of 0.1 wt% were added, and the temperature was raised to 80 °C with stirring, and activated at this temperature for about 45 min; 3.0 g (0.02 mol) of vinyltrimethoxysilane was added to the three-necked flask through a syringe pump over 15 min. After the addition of vinyltrimethoxysilane, the reaction mixture was reacted at 80 °C for 6 h; S4: After the reaction of S3 is completed, the crude reaction product is cooled to room temperature, and 0.05 g of aniline is added to the crude reaction product to inactivate the residual platinum catalyst; the reaction mixture is then subjected to reduced pressure distillation at a pressure of -100 kPa and 160 °C to remove low-boiling substances to obtain 29.77 g of light yellow, clear and transparent double-end dimethylvinylsiloxy-terminated trimethoxy-functionalized polysiloxane, with a yield of 95.5%. Its chemical structure is shown in Formula (V).
[0082] (V) Wherein m is the degree of polymerization of the dimethylsiloxy chain segment.
[0083] The product prepared in Example 6 was 1 H NMR analysis, the results are as follows Figure 4 The peak with a chemical shift of about δ = 0.068 ppm is all methyl groups connected to silicon atoms (Si-C H3) The proton peak on the molecule, with a chemical shift of about δ = 0.41 ~ 0.58 ppm, is the characteristic peak of the anti-Markovnikov addition product, the chemical shift of about δ = 1.12 ppm is the characteristic peak of the Markovnikov addition product, and the chemical shift of δ = 3.56 ppm is the chemical shift of the proton on the trimethoxy group (-Si-OC H 3), chemical shifts in the range of δ = 5.7 ~ 6.16 ppm are chemical shifts of protons on vinyl (Si-C H =C H 2). Si-OC H The integral area of 3 is defined as 9, and the proton peak area of all silicon methyl groups is 293.1. According to the formula for calculating the structural polymerization degree m, 3+2×(6m+6)=293.1, we get m≈23.
[0084] Product 29 Si NMR spectrum Figure 5 As shown, the chemical shift at δ = 8.2 ppm is -O- Si The characteristic peak of silicon atom in (CH3)-CH2-CH2-, the chemical shift is -O- at δ = -4.1 ppm Si The characteristic peak of silicon atom in (CH3)2CH=CH2, the peak with chemical shift around δ=-21.9 ppm is -O- Si The characteristic peak of silicon atom in -(CH3)2-O-, chemical shift is - at δ=-41.4ppm. Si -Characteristic peaks of silicon atoms in (OCH3)3.
[0085] GPC analysis of the product showed that the number average molecular weight (Mn) of the polymer was 2652 g / mol, and the polydispersity index (PDI) was 1.22. The viscosity of the polymer at 25 °C was 37.50 mPa·s as measured by a rotational viscosity instrument.
[0086] The trimethoxy-functionalized polysiloxane terminated with dimethylvinylsiloxy groups and having a polymerization degree of m=23 prepared in Example 6 was used to replace the trimethoxy-functionalized polysiloxane terminated with trimethylsiloxy groups and having a polymerization degree of m=3 in Example 1 as the surface treatment agent for the alumina filler. The rest of the steps were the same as in Example 1 to prepare the thermal conductive silicone paste sample of Example 6, and its performance test data are shown in Table 1.
[0087] Example 7 Preparation of methoxy-functionalized polydiethylsiloxane terminated with diethylbutylsiloxy groups having a polymerization degree of m=6 S1: In a 1L dry three-necked flask at -10°C under nitrogen protection, add 50.0 mL of tetrahydrofuran with a water content of less than 200 ppm under stirring, then add 43.5 mL (0.11 mol) of a 2.5 mol / L n-butyl lithium n-hexane solution into the three-necked flask, stir and maintain at this temperature for 30 min; add a mixed solution consisting of 100.0 g (0.33 mol) of hexaethylcyclotrisiloxane and 50.0 mL of tetrahydrofuran with a water content of less than 200 ppm into the three-necked flask over 25 min, after the addition of the THF solution of hexaethylcyclotrisiloxane is completed, raise the temperature of the reaction mixture to 25°C, and continue the reaction at this temperature for 24 h; when the raw material point disappears as monitored by thin layer chromatography (TLC), add 7.81 g (0.055 mol) of methylvinyldichlorosilane (MeViSiCl2) for bridging reaction, and the addition time is 20 min; after the addition of methyldichlorosilane was completed, the reaction mixture was allowed to react at 25 °C for 90 min.
[0088] S2: The crude product of the reaction obtained in S1 was subjected to vacuum distillation for 2 h from room temperature to 70 °C at a pressure of -85 kPa. After removing low boiling point solvents such as tetrahydrofuran, the liquid in the kettle was cooled to room temperature. After removing the generated salt by vacuum filtration, the obtained colorless transparent mixed solution was subjected to vacuum distillation for 5 h at a pressure of -100 kPa and 170 °C to remove impurities. After cooling to room temperature, 109.24 g of colorless transparent double-end diethylbutylsiloxy-terminated Si-Vi functionalized polydiethylsiloxane intermediate was obtained with a yield of 82.6%. Its chemical structure is shown in formula (VI).
[0089] (VI) Wherein m represents the degree of polymerization of the diethylsiloxy chain segment.
[0090] S3: Dry nitrogen was introduced into a dry 100 mL three-necked flask, and then 30.0 g of the Si-Vi functionalized polydiethylsiloxane intermediate capped with diethyl n-butylsiloxy groups obtained in step S2 and 0.68 g (the effective content of platinum atoms was 20 ppm) of Karstedt catalyst with a platinum content of 0.1 wt% were added, and the temperature was raised to 75 °C with stirring, and activated at this temperature for about 35 min; 3.6 g (0.029 mol) of trimethoxysilane was added to the three-necked flask through a syringe pump over 20 min. After the addition of trimethoxysilane, the reaction mixture was reacted at 75 °C for 5 h; S4: After the reaction of S3 is completed, the crude reaction product is cooled to room temperature, and 0.05 g of aniline is added to the crude reaction product to inactivate the residual platinum catalyst; the reaction mixture is then subjected to reduced pressure distillation at -100 kPa and 150 °C to remove low-boiling substances to obtain 31.03 g of light yellow, clear and transparent double-end diethyl-n-butylsilyloxy-capped trimethoxy-functionalized polydiethylsiloxane, with a yield of 96.5%. Its chemical structure is shown in Formula (VII).
[0091] (VII) Wherein m is the degree of polymerization of the dimethylsiloxy chain segment.
[0092] The product prepared in Example 7 was 1 H NMR analysis, the results are as follows Figure 6 The peaks with chemical shifts around δ = 0.074 ~ 0.15 ppm are all methyl groups connected to silicon atoms (Si-C H 3) The proton peak on the surface has a chemical shift of -Si-CH2CH2C at about δ=0.49~0.52 ppm H 2CH3, -Si-CH2C H 3 and the characteristic peak of the anti-Markovnikov addition product, the chemical shift at δ = 0.93 ppm is -Si-CH2CH2CH2C H 3 and -Si-CH2C H The characteristic peak of 3, with a chemical shift of about δ=1.31 ppm, is Si-C H 2C H The characteristic peaks of 2CH2CH3 and anti-Markovnikov addition products, the chemical shift at δ = 3.49 ~ 3.55 ppm is the chemical shift of the proton on the trimethoxy group (-Si-OC H 3). Si-OC H The integral area of 3 is defined as 9, then Si-CH2C H3 The integrated area of the proton peak is 82.3-12=70.3. According to the formula for calculating the structural polymerization degree m value 2×6m=70.3, it can be calculated that m≈6;
[0093] product 29 Si NMR spectrum Figure 7 The chemical shift at δ = 8.2 ppm is -O- Si The characteristic peak of silicon atom in (CH3)-CH2-CH2-, the peak with chemical shift around δ=-22.9 ppm is -O- Si The characteristic peak of silicon atom in -(Et)2-O-, with chemical shift at δ=-37.3 ppm, is the M chain -O- SiThe characteristic peak of silicon atom in (Et)2(n-Bu) has a chemical shift of -41.5 ppm. Si -Characteristic peaks of silicon atoms in (OCH3)3.
[0094] GPC analysis of the product showed that the number average molecular weight of the polymer was 1885 g / mol and the polydispersity index (PDI) was 1.29. The viscosity of the polymer at 25°C was 28.25 mPa·s as measured by a rotational viscosity instrument.
[0095] The trimethoxy-functionalized polydiethylsiloxane terminated with diethyl-n-butylsiloxy groups and having a polymerization degree of m=6 prepared in Example 7 was used to replace the trimethoxy-functionalized polysiloxane terminated with trimethylsiloxy groups and having a polymerization degree of m=3 in Example 1 as the surface treatment agent for the alumina filler. The rest of the steps were the same as in Example 1 to prepare the thermal conductive silicone paste sample of Example 7, and its performance test data are shown in Table 1.
[0096] Comparative Example 1: No surface treatment agent is added in the preparation of silicone paste Add 2.88 g of dimethyl silicone oil with a viscosity of 350 mPa.s at 25°C, 48.40 g of Al2O3 particles with an average particle size of 120 μm, 26.40 g of Al2O3 particles with an average particle size of 10 μm, and 13.20 g of Al2O3 particles with an average particle size of 0.5 μm to the mixing cup. The density of all polysiloxane fluids is 0.98 g / cm 3 The density of Al2O3 thermal conductive fillers of various particle sizes is calculated according to 4.0 g / cm 3 Calculation shows that the volume fraction of alumina filled in the silicone paste is 88 vol%.
[0097] The mixing cup was placed on the sample fixture of the non-intrusive homogenizer, and mixed for 3 min at a speed of 1800 rpm and reduced pressure to -99.5 kPa to obtain a comparative thermal conductive silicone paste sample, whose performance test data is shown in Table 1.
[0098] Comparative Example 2: Adding KH-550 as a filler surface treatment agent in the preparation of silicone paste Add 1.76 g of γ-aminopropyltriethoxysilane (KH-550), 1.12 g of dimethyl silicone oil with a viscosity of 350 mPa.s at 25°C, 48.40 g of Al2O3 particles with an average particle size of 120 μm, 26.40 g of Al2O3 particles with an average particle size of 10 μm, and 13.20 g of Al2O3 particles with an average particle size of 0.5 μm to the mixing cup. The density of all polysiloxane fluids is 0.98 g / cm 3 The density of Al2O3 thermal conductive fillers of various particle sizes is calculated according to 4.0 g / cm3 Calculation shows that the volume fraction of alumina filled in the silicone paste is 88 vol%.
[0099] The mixing cup was placed on the sample fixture of the non-intrusive homogenizer, and mixed for 3 min at a speed of 1800 rpm and reduced pressure to -99.5 kPa to obtain a thermal conductive silicone paste sample of Comparative Example 2, whose performance test data is shown in Table 1.
[0100] Comparative Example 3: Single-end alkoxy-terminated polysiloxane (m=19) was added as a filler surface treatment agent in the preparation of silicone paste The structure of single-end alkoxy-terminated polysiloxane is as follows: (VIII) 1.76 g of the single-end alkoxy-terminated polysiloxane of the structure shown in Comparative Example 3, 1.12 g of dimethyl silicone oil with a viscosity of 350 mPa.s at 25°C, 48.40 g of Al2O3 particles with an average particle size of 120 μm, 26.40 g of Al2O3 particles with an average particle size of 10 μm, and 13.20 g of Al2O3 particles with an average particle size of 0.5 μm were added to the mixing cup. The density of all polysiloxane fluids was 0.98 g / cm 3 The density of Al2O3 thermal conductive fillers of various particle sizes is calculated according to 4.0 g / cm 3 Calculation shows that the volume fraction of alumina filled in the silicone paste is 88 vol%.
[0101] The mixing cup was placed on the sample fixture of the non-intrusive homogenizer, and mixed for 3 min at a speed of 1800 rpm and reduced pressure to -99.5 kPa to obtain a thermal conductive silicone paste sample of Comparative Example 3, whose performance test data is shown in Table 1.
[0102] Table 1 Performance test results of various embodiments and comparative examples serial number <![CDATA[Thermal resistance (K·cm 2 / W)]]> Thermal conductivity (W / (m·K) 1 / 4 cone penetration (0.1mm) Silicone paste appearance Example 1 4.7040 7.8560 31.9 Paste Example 2 3.5330 8.8300 47.4 Paste Example 3 3.3133 9.1190 54.7 Paste Example 4 3.5800 8.6180 51.0 Paste Example 5 4.1333 8.4650 47.7 Paste Example 6 4.4300 7.6450 45.9 Paste Example 7 3.3325 8.5330 48.3 Paste Comparative Example 1 / / / Loose powder Comparative Example 2 5.9217 6.6330 26.3 Paste-like, with obvious grainy texture on the surface Comparative Example 3 3.3825 8.3580 50.3 Paste It can be seen from the test data in Table 1 that when the filling volume fraction of mixed-size Al2O3 particles is 88%, the thermal conductive silicone paste prepared without using a silane coupling agent (Comparative Example 1) cannot be formed and is in a loose powder state; when the commercial silane coupling agent KH-550 is used as a filler surface treatment agent, the prepared thermal conductive silicone paste with a filling load of 88 vol% can form a paste, but there is an obvious granular feeling on the surface, and the thermal conductivity of the prepared silicone paste is 6.6330 W / (m·K), and the thermal resistance is 5.9217 K·cm 2 / W.
[0103] At the same thermal conductive filler filling volume fraction, when the products prepared in the embodiments of the present application are used as filler surface treatment agents, the prepared samples are in a paste state, and the thermal conductivity and cone penetration are significantly higher than those of Comparative Example 2, and the thermal resistance is significantly lower than that of Comparative Example 2. This is mainly because the alkoxy active groups in the surface treatment agent react with the hydroxyl groups on the surface of the Al2O3 particles, allowing the hydrophobic organic segments to be effectively grafted on their surface. These longer Si-O-Si segments also improve the compatibility between the Al2O3 particles and the polysiloxane matrix, allowing the filler to be better dispersed in the system. This uniform dispersion is conducive to forming a continuous heat conduction path, thereby improving the thermal conductivity.
[0104] It can be seen from Example 3 and Comparative Example 3 that the degree of polymerization m in Example 3 of the present invention is 8, and the number of repeating units of the dimethylsiloxy chain segment in the trimethoxy-functionalized polydimethylsiloxane terminated with trimethylsiloxy groups at both ends is 16; the degree of polymerization m of the structure shown in Comparative Example 3 is 19, which is similar to the degree of polymerization of the product obtained in Example 3 of the present application, and the molecular weight is slightly different. The content of trimethoxy groups contained in the two is not much different, but the three methoxy groups in Example 3 are located at the side group part of the central silicon atom of the polymer, and the three methoxy groups in Comparative Example 3 are located at an end group of the polymer molecule. It can be seen that the trimethoxy functional group in a special position in Example 3 significantly improves the thermal conductivity and cone penetration of the silicone paste.
[0105] The above describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and the specification only describe the principles of the present application. The present application may have various changes and improvements without departing from the spirit and scope of the present application, and these changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection claimed by the present application is defined by the attached claims and their equivalents.
Claims
1. A trialkoxy-functionalized polysiloxane, characterized in that: It has the following structural formula: Among them, R a is one of methyl, ethyl, phenyl, vinyl, butyl or trimethylsilyl; R b is at least one of methyl, ethyl, phenyl or trifluoropropyl; R c is at least one of methyl, ethyl, phenyl or trifluoropropyl, R d is at least one of methyl, ethyl, propyl or phenyl, R e is methyl or ethyl; m is R b R c The degree of polymerization of the SiO chain segment, m, is 2~500.
2. The trialkoxy-functionalized polysiloxane according to claim 1, characterized in that The R a is methyl, vinyl or butyl, R b , R c , R d is methyl or ethyl, R e It is methyl.
3. The trialkoxy-functionalized polysiloxane according to claim 1, characterized in that m is 2~50.
4. The method for preparing a trialkoxy-functionalized polysiloxane according to any one of claims 1 to 3, characterized in that: Includes steps: Step 1, alkyl lithium RaLi is activated in a solvent, and a solution of cyclotrisiloxane represented by formula I is added to perform polymerization reaction to obtain intermediate A, and after the reaction is completed, a solution of dichlorosilane represented by formula II is added to continue the reaction, and intermediate B is obtained by purification; Step 2, activating the intermediate B and the Custer catalyst, adding trialkoxysilane YSi(ORe)3 to catalyze the reaction, and purifying to obtain the trialkoxy functionalized polysiloxane; wherein Ra, Rb, Rc, Rd and Re are as described in claim 1, m is 2 to 500, and X and Y are H or vinyl, which are different.
5. The method for preparing a trialkoxy-functionalized polysiloxane according to claim 4, characterized in that: In step 1, the solvent of alkyl lithium RaLi, cyclotrisiloxane and dichlorosilane is an ether solvent; the ether solvent includes at least one of diethyl ether, dimethyl ether, diethoxymethane, tetrahydrofuran, methyltetrahydrofuran and 1,4-dioxane.
6. The method for preparing trialkoxy-functionalized polysiloxane according to claim 1, characterized in that: The alkyl lithium RaLi includes at least one of methyl lithium, ethyl lithium, phenyl lithium, n-butyl lithium, dimethyl vinyl silicon alkoxide lithium, and trimethylsilyl methyl lithium; The cyclotrisiloxane is selected from at least one of hexamethylcyclotrisiloxane, hexaethylcyclotrisiloxane, 1,3,5-trimethyl-1,3,5-triethylcyclotrisiloxane, 1,3,5-trimethyl-1,3,5-triphenylcyclotrisiloxane, and hexaphenylcyclotrisiloxane; The dichlorosilane is selected from at least one of methyldichlorosilane, methylvinyldichlorosilane, ethyldichlorosilane, ethylvinyldichlorosilane, phenyldichlorosilane and phenylvinyldichlorosilane.
7. The method for preparing trialkoxy-functionalized polysiloxane according to claim 1, characterized in that: In step 1, the polymerization reaction temperature is 15-50°C and the reaction time is 4-36 h; The molar ratio of the alkyl lithium to the cyclotrisiloxane is 1:0.1 to 1:120; The molar ratio of dichlorosilane to alkyl lithium is 0.25-0.75:1, the addition time of dichlorosilane is 2-60 min, and the continuation time after adding dichlorosilane is 10-180 min.
8. The method for preparing trialkoxy-functionalized polysiloxane according to claim 1, characterized in that: In step 2, the molar ratio of trialkoxysilane to intermediate B is 1.35-2.00:1; The catalyst activation temperature is 60~90℃; the activation time is 20~60 min; The catalytic reaction temperature is 60~90℃ and the reaction time is 1~12h.
9. The method for preparing trialkoxy-functionalized polysiloxane according to claim 1, characterized in that: The mass of platinum in the Custer catalyst is 2.5×10 -6 ~100×10 -6 ; After the reaction in step 2 is completed, an organic amine is added to deactivate the catalyst, and the organic amine is selected from at least one of triethylamine, ethylenediamine, diethylamine, and aniline; the mass is 3.0×10 of the total mass of the reaction raw materials -4 ~50×10 -4 .
10. A thermal interface material, characterized in that: The invention comprises a polydimethylsiloxane terminated with trimethylsiloxy groups at both ends, an alumina filler and the trialkoxy-functionalized polysiloxane according to any one of claims 1 to 3.
Citation Information
Patent Citations
Thermal interface material as well as preparation method and application thereof
CN118085295A
Cited By
Low-temperature-resistant adhesive and preparation method thereof
CN120005555A
Anti-dripping phosphorus-silicon composite flame retardant and preparation method thereof
CN122188161A